The Development of Prototype Micro Hydropower System with Internet of Things (IoT) Feature - Abd Razak, Nurul Izzah; Lam, Hong Yin (Progress in Engineering Application and Technology, 2023)
This project involved designing, creating, and testing a prototype micro hydropower system that incorporates Internet of Things (IoT) features, aiming to provide efficient energy generation and management. Recognizing an urgent need for reliable, energy-efficient and easily maintained micro hydropower solutions, this project sought to produce a system capable of yielding a maximum output capacity of 300W, ideal for powering remote communities, households, and small enterprises. The methodology included selecting suitable hardware and software components and integrating IoT technology for remote, real-time monitoring and control of the system. Rigorous testing was performed to verify the system’s performance. The completed project resulted in a micro hydropower system demonstrating the expected maximum output capacity and effective compatibility with IoT for remote access, a clear indication of the potential of advanced technology in renewable energy. This project’s success marks a significant step towards a future powered by sustainable and renewable energy alternatives, particularly demonstrating the potential of micro hydropower systems in off-grid locations. Furthermore, this project serves as an impetus for more research and implementation in renewable energy technologies, reinforcing the viability and impact of such systems in transforming energy generation and consumption.